(NmAGNITNYE POLQ GALAKTIK (B/s - (NrUZMAJKIN(B, (NaLEKSANDR aNDREEWI^s; (NsOKOLOW(B, (NdMITRIJ dMITRIEWI^s; (N{UKUROW(B, (NaNWAR mUHAMADOWI^s ((NmOSKWA (B:s (NnAUKA(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 253-279s
Keywords: (NgALAKTIKI (B- (NmAGNITNOE POLEs